(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
This research was carried out during November - December 2020 on the KM ship. Woka Ruju 01 as many as 35 trips, with the aim of estimating and analyzing the effect of the speed of looping and pulling the rope on the number of fish catches. The use of experimental fishing methods and data analysis using multiple linear regression are expected to answer the research objectives. The results of the research that the results of the study were obtained that together the second factor or variable looping time and pulling the corrugated rope had a significant effect on the catch of small pelagic fish with an Fcount value of 9.908 and a significance value of 0.007 less than 0.05, with the regression model formed. is Y = 3.410 – 2.181X1 + 0.016X2, while individually using the exponential regression equation it is found that only the looping time of the purse seine fishing gear has a significant effect on the catch of small pelagic fish with a correlation coefficient of -0.842 and a t-test value of -4.423 and significance value 0.02 is smaller than 0.05.